PENERAPAN AKHLAK DALAM BERBAGAI AKTIVITAS KEHIDUPAN DAN PENDIDIKAN AGAMA ISLAM - Syi'bul Huda, Ali Anhar (MGMP PAI Jawa Barat, 2023)
Morals are an important part of the human being because they greatly affect various dimensions of life. This is in line with the main prophetic mission of the Prophet Shalaullahu'alaihi Wassalam, which is to improve, and perfect human morals and save them from the abyss of ugliness that can destroy them. The main purpose of the moral improvement carried out by him was because in the early pre-Islamic era, immoral actions covered all human activities at that time, so in the framework of Allah's compassion, He sent a messenger from among his people to guide them to the path of truth. Therefore, the research aims to understand as well as describe the dimensions of morals and the application of morals in everyday life specifically in Islamic Religious Education activities. The research method used is using a qualitative approach with a literature study method, the data analysis is descriptive, and the data source consists of primary data in the form of journals, proceedings, papers, books, and reports while secondary data is documentation and credible internet sources. The results revealed that the moral dimension consists of morals to oneself, morals to Allah as Rabb, and morals to nature. The morals applied in life include keeping oneself from fasad actions, honing one's skills, always worshiping Him, helping others, and protecting the environment.